Prolactin-Induced Adaptation in Glucose Homeostasis in Mouse Pregnancy Is Mediated by the Pancreas and Not in the Forebrain - Khant Aung, Zin; Kokay, Ilona C.; Grattan, David R.; Ladyman, Sharon R. (Frontiers in Endocrinology, 2021)
Adaptive changes in glucose homeostasis during pregnancy require proliferation of insulin-secreting beta-cells in the pancreas, together with increased sensitivity for glucose-stimulated insulin secretion. Increased concentrations of maternal prolactin/placental lactogen contribute to these changes, but the site of action remains uncertain. Use of Cre-lox technology has generated pancreas-specific prolactin receptor (Prlr) knockouts that demonstrate the development of a gestational diabetic like state. However, many Cre-lines for the pancreas also express Cre in the hypothalamus and prolactin could act centrally to modulate glucose homeostasis. The aim of the current study was to examine the relative contribution of prolactin action in the pancreas and brain to these pregnancy-induced adaptations in glucose regulation. Deletion of prolactin receptor (Prlr) from the pancreas using Pdx-cre or Rip-cre led to impaired glucose tolerance and increased non-fasting blood glucose levels during pregnancy. Prlrlox/lox/Pdx-Cre mice also had impaired glucose-stimulated insulin secretion and attenuated pregnancy-induced increase in beta-cell fraction. Varying degrees of Prlr recombination in the hypothalamus with these Cre lines left open the possibility that central actions of prolactin could contribute to the pregnancy-induces changes in glucose homeostasis. Targeted deletion of Prlr specifically from the forebrain, including areas of expression induced by Pdx-Cre and Rip-cre, had no effect on pregnancy-induced adaptations in glucose homeostasis. These data emphasize the pancreas as the direct target of prolactin/placental lactogen action in driving adaptive changes in glucose homeostasis during pregnancy.